2005
DOI: 10.1680/geot.2005.55.4.325
|View full text |Cite
|
Sign up to set email alerts
|

Effect of confining pressure on the degradation of ballast under cyclic loading

Abstract: Traditional railway foundations or substructures have become increasingly overloaded in recent years due to the introduction of faster and heavier trains. A lack of substructure re-engineering has resulted in maintenance cycles becoming more frequent and increasingly expensive. Two significant problems arising from increasing axle loads are differential track settlement and ballast degradation. The results suggest that in-situ lateral pressures should be increased to counteract the axle loads of heavier trains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
88
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(100 citation statements)
references
References 19 publications
11
88
0
1
Order By: Relevance
“…After each test was completed, crib ballast and load-bearing ballast aggregates were recovered from the triaxial chamber separately and then sieved to determine any changes in particle gradation. The breakage was quantified using the parameter ballast breakage index (BBI), proposed by Indraratna et al (2005). By using a hypothetical linear size axis as a reference, the BBI then was calculated using Eq.…”
Section: Ballast Breakagementioning
confidence: 99%
“…After each test was completed, crib ballast and load-bearing ballast aggregates were recovered from the triaxial chamber separately and then sieved to determine any changes in particle gradation. The breakage was quantified using the parameter ballast breakage index (BBI), proposed by Indraratna et al (2005). By using a hypothetical linear size axis as a reference, the BBI then was calculated using Eq.…”
Section: Ballast Breakagementioning
confidence: 99%
“…The coefficient of uniformity (c uf ) of different ballast samples after the testing ranged from 1.89-1.94 in comparison to an initial c u of 1.87 (Table 4). Their corresponding ballast breakage indices (BBI, after Indraratna et al 2005) ranged from 4.6 to 11.0%, as reported by Indraratna et al (2013). The generation of fines of different sizes as a result of particle breakage makes the sample well-graded, with the ones undergoing higher particle breakage exhibiting a higher value of c uf .…”
Section: Influence Of Loading On the Psd Of Ballastmentioning
confidence: 70%
“…It is well known that rearrangement of particles upon loading lead to their breakage (Indraratna et al 2005 andLackenby et al 2007), the extent of which directly determines the design life of ballast. Therefore, it is essential to lessen the particle breakage to enhance the ballast life, and thereby minimise the need for frequent ballast replacements.…”
Section: Optimum Geogrid Placement Position To Minimise Particle Breamentioning
confidence: 99%
“…1, Indraratna et al, 2005). Here, the arbitrary boundary of maximum breakage is fixed depending on the grading of the specimen after shearing.…”
Section: Methodsmentioning
confidence: 99%
“…In this range, the volumetric behaviour changes from mainly dilation at low confining pressure to compression with the increasing confining pressure. Past experimental and DEM studies on coarse granular materials conducted at University of Wollongong have shown that in the early dilation stage, particle degradation is mainly associated with the breakage of sharp corners of the angular particles, and then followed by a stage where densification (overall compression) occurs with much less breakage (Indraratna et al, 2005 andHossain et al 2007). However, as the confining pressure is increased considerably, dilation is prevented and the particle assembly undergoes increased compression and associated breakage occurs across the middle part of the grains and not just at the corners (Indraratna et al 2010 andIndraratna et al 2014).…”
Section: Stress-strain Behaviour and Associated Breakagementioning
confidence: 99%